Pengembangan Alat Tanam Benih Padi Langsung (ATABELA) Metode Vakum - Muhammad Tahir Sapsal; Muhammad Fadlian; Salengke Salengke (Jurnal Agritechno, 2021)
Direct seed planting tools or commonly abbreviated as ATABELA have been commonly used in rice cultivation in Indonesia. One of the problems that often occur in the use of this tool is the inconsistency in the number of seeds released. Besides, the seeds that are issued are usually more than three seeds, so that it can cause competition in the growth process. Therefore, it is necessary to develop direct seed planting tools with precise seed dosage. This study aims to design an applicator for planting rice seeds directly by dropping the seeds using vacuum pressure. Another goal is to know the pressure that can be generated as well as the forward speed required to produce the desired vacuum pressure. The first step in this research is to identify the pressure needed to move the seeds, then design a tool based on the pressure data. The test is carried out using a DC motor as a substitute for wheel rotation to determine the forward speed required to obtain the required pressure. The moisture content of the seeds used is 22.71% and the required pressure is 97 kPa (4 kPa under standard atmospheric pressure), the required forward speed is 2.5 m / s, so it is necessary to modify the ratio of the wheel pulley to the drive shaft.